Nickel-based catalyst as well as preparation method and application thereof
By preparing the nickel-based catalyst with Ni-NiFe alloy structure, the problems of short life of existing catalysts under high temperature conditions and nickel grain aggregation are solved, and high temperature activity and carbon nanotube morphology are improved.
Patent Information
- Application Number
- CN202411802043.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-09
AI Technical Summary
During the methane cracking process, existing nickel-based catalysts have problems of aggregation and inactivation of nickel grains under short life and high temperature conditions.
By preparing a nickel-based catalyst, using materials such as ammonia water, nickel salt, iron salt, citric acid and support ethyl orthosilicate, an alloy structure of Ni-NiFe is formed, and the equilibrium between carbon atom generation, diffusion and precipitation rates are maintained, and Ni grain agglomeration is restricted.
The high-temperature activity and life of the nickel-based catalyst are improved, and the morphology of the carbon nanotubes produced is improved, with few branches, longer length and strong continuity.
Smart Images

Figure CN119608168A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of methane cracking catalysis, and in particular to a nickel-based catalyst for preparing carbon nanotubes by cracking methane, and a preparation method and application thereof. Background Art
[0002] Methane cracking is an important way to prepare carbon nanotubes, and catalysts are the core technology of the methane cracking process, and nickel-based catalysts are the main catalysts for methane cracking to produce carbon nanotubes. Nima Bayat, Gaowei Wang and others used the impregnation method and co-precipitation method to prepare Ni-Fe-Al catalysts to form Ni-Fe alloys. The results showed that the addition of an appropriate amount of Fe can increase the diffusion rate of carbon and reduce the formation rate of carbon. This maintains the balance between the generation, diffusion and precipitation rates of carbon atoms and enhances the stability of the catalyst. However, the catalyst still has the problem of short life due to graphite carbon covering the active center and deactivation due to aggregation of nickel grains under high temperature conditions. Summary of the invention
[0003] The present invention creatively prepares a catalyst for the reaction of preparing carbon nanotubes by cracking methane. In the catalyst, a special force is formed between the metal Ni and the NiFe alloy, forming a Ni-NiFe alloy structure, maintaining the balance between the generation, diffusion and precipitation rates of carbon atoms, improving the morphology of carbon nanotubes, effectively limiting the agglomeration between Ni grains, and improving the high-temperature activity and life of the nickel-based catalyst.
[0004] One of the purposes of the present invention is to provide a method for preparing a nickel-based catalyst.
[0005] A second object of the present invention is to provide a nickel-based catalyst prepared by the preparation method.
[0006] The third object of the present invention is to provide an application of the nickel-based catalyst.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] In a first aspect, the present invention provides a method for preparing a nickel-based catalyst, comprising the following steps:
[0009] S1, heating ammonia water to obtain solution a;
[0010] S2, mixing and heating nickel salt, iron salt, water and citric acid to prepare solution b (i.e., a complex aqueous solution of nickel salt and iron salt), wherein the molar ratio of Ni to Fe is 5:1 to 5:3, and the molar ratio of citric acid to metal salt (i.e., the sum of nickel salt and iron salt) is 1:10 to 3:10;
[0011] S3, mixing ethyl orthosilicate and anhydrous ethanol and heating them to prepare solution C;
[0012] S4. Add solution c to solution b, mix and heat, then add solution a, mix and heat until the mixed solution becomes viscous, dry, and calcine in a mixed atmosphere of N2 and H2 to obtain a nickel-based catalyst.
[0013] Step S1:
[0014] Industrial ammonia is an aqueous solution containing 25% to 28% ammonia;
[0015] In some embodiments, in step S1, the heating temperature is 60°C to 80°C.
[0016] Step S2:
[0017] In some embodiments, in step S2, the nickel salt includes one or more of nickel nitrate, nickel sulfate, and nickel acetate; the iron salt includes one or more of iron nitrate, iron sulfate, and iron acetate.
[0018] In some embodiments, in step S2, the mass ratio of the metal salt to water is 0.2 to 0.4;
[0019] In some embodiments, in step S2, the heating temperature is 60°C to 80°C.
[0020] Step S3:
[0021] In some embodiments, in step S3, the mass ratio of tetraethyl orthosilicate to anhydrous ethanol is 1 to 3;
[0022] In some embodiments, in step S3, the heating temperature is 60°C to 80°C.
[0023] Step S4:
[0024] In some embodiments, in step S4, the ratio of ethyl orthosilicate, metal salt and ammonia water in the mixed solution is 90-140 g: 180-260 g: 16-36 mL;
[0025] In some embodiments, in step S4, the heating temperature after adding solution c to solution b is 60° C. to 80° C.;
[0026] In some embodiments, in step S4, the heating temperature after adding solution a is 60° C. to 800° C.;
[0027] In some embodiments, in step S4, the drying temperature is 100 to 120° C., and the drying time is 12 to 24 hours;
[0028] In some embodiments, in step S4, the volume ratio of N2 to H2 is 4:1 to 10:1;
[0029] In some embodiments, in step S4, the calcination temperature is 650-850° C., and the calcination time is 4-6 hours.
[0030] In some specific embodiments, the method for preparing a nickel-based catalyst comprises the following steps:
[0031] (1) Take a certain amount of ammonia water and heat it in a water bath to 60℃~80℃, which is called solution a;
[0032] (2) taking a certain amount of Ni and Fe salts respectively, adding a certain amount of deionized water and citric acid, stirring, heating in a water bath to 60°C to 80°C to dissolve and prepare a Ni and Fe salt complex solution, which is recorded as solution b; the molar ratio of Ni to Fe is 5:1 to 5:3, and the molar ratio of citric acid to metal salt is 1:10 to 3:10;
[0033] (3) Take a certain amount of carrier ethyl orthosilicate, add a certain amount of anhydrous ethanol, stir, and heat in a water bath to 60°C to 80°C to disperse the ethyl orthosilicate, which is recorded as solution C;
[0034] (4) Slowly add solution c into solution b, stir and heat the mixed solution in a water bath at 60°C to 80°C, then slowly add solution a into the mixed solution, stir and heat in a water bath at 90°C to 100°C until the mixed solution becomes viscous, dry at 100°C to 120°C for 12 to 24 hours, and calcine at 650 to 850°C for 4 to 6 hours in an atmosphere of a mixture of N2 and H2 to obtain a nickel-based catalyst, denoted as Ni-NiFe / SiO2.
[0035] In a second aspect, the present invention provides a nickel-based catalyst prepared by the above preparation method.
[0036] The obtained nickel-based catalyst includes a carrier SiO2 and Ni nanoparticles and NiFe alloy nanoparticles loaded thereon, and a special force is formed between Ni and NiFe alloy to form a Ni-NiFe alloy structure.
[0037] In a third aspect, the present invention provides a use of the above nickel-based catalyst in preparing carbon nanotubes by cracking methane.
[0038] Preferably, the application includes: placing the catalyst in a reactor, introducing a mixture of N2 and H2 for reduction for 0.5-1.5 hours, then introducing a mixture of raw materials CH4 and N2 for reaction to crack the catalyst to generate carbon nanotubes, and introducing nitrogen after the reaction to purify the carbon nanotubes;
[0039] The reaction conditions are: reaction temperature is 700-800°C, reaction pressure is 0.1-0.2MPa, volume space velocity is 400-600h -1 , the volume ratio of N2 to CH4 is 4:1 to 1:1.
[0040] The catalyst of the present invention can generate carbon nanotubes with fewer branches, longer length and stronger continuity.
[0041] Technical effects:
[0042] The present invention creatively prepares a Ni-NiFe catalyst for methane cracking reaction to produce high value-added carbon nanotubes. A special force is formed between the metal Ni and the NiFe alloy in the catalyst, forming a Ni-NiFe alloy structure, maintaining the balance between the generation, diffusion and precipitation rates of carbon atoms, improving the morphology of carbon nanotubes, effectively limiting the agglomeration between Ni crystal grains, and improving the high temperature activity and life of the nickel-based catalyst.
[0043] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is the XRD pattern of the catalyst prepared in Example 1, where the right picture is a partial enlarged picture of the left picture;
[0045] Figure 2 The catalyst TPR spectra of the embodiments and comparative examples are shown in FIG.
[0046] Figure 3 TEM image of carbon nanotubes generated by the reaction of the catalyst in Example 1;
[0047] Figure 4 TEM image of carbon nanotubes generated by the reaction of the catalyst in Comparative Example 1;
[0048] Figure 5 This is a SEM image of carbon nanotubes produced by reaction with NiFe / Al2O3, a technical background Nima Bayat catalyst;
[0049] Figure 6 This is a SEM image of carbon nanotubes generated by the reaction using the catalyst in Example 1. DETAILED DESCRIPTION
[0050] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0051] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0052] Example 1
[0053] Take 32 ml of ammonia water (aqueous solution containing 25% ammonia) and heat it to 80°C in a water bath, which is called solution a.
[0054] Take 145g Ni(NO3)2·6H2O and 75g Fe(NO3)3·9H2O respectively, add 630g deionized water and 26g citric acid (the molar ratio of Ni to Fe is 5:2, and the molar ratio of citric acid to metal salt is 2:10), stir, heat in a water bath to 80℃ to dissolve and prepare Ni and Fe salt complex solution, recorded as solution b;
[0055] Take 115g of carrier ethyl orthosilicate, add 115g of anhydrous ethanol, stir, heat in a water bath to 80°C to disperse the ethyl orthosilicate, and record it as solution C;
[0056] Slowly add solution c to solution b, stir and heat the mixed solution in a water bath at 80°C, then slowly add solution a to the mixed solution, stir and heat the mixed solution in a water bath at 100°C until the mixed solution becomes viscous, dry at 120°C for 24 hours, and calcine at 750°C for 4 hours in an atmosphere of N2 and H2 mixed gas (N2 and H2 volume ratio is 9:1) to obtain Ni-NiFe / SiO2 catalyst. Its XRD pattern is shown as follows: Figure 1 As shown, it can be seen that the characteristic peak of metallic nickel is at 2θ=44.0, and the NiFe alloy structure is at 2θ=44.6. The characteristic peak of metallic iron has not been found. Therefore, the Ni-NiFe / SiO2 catalyst is obtained.
[0057] Example 2
[0058] Take 28 ml of ammonia water (aqueous solution containing 25% ammonia), heat it to 80°C in a water bath, and record it as solution a;
[0059] Take 145g Ni(NO3)2·6H2O and 37g Fe(NO3)3·9H2O respectively, add 530g deionized water and 23g citric acid (the molar ratio of Ni to Fe is 5:1, and the molar ratio of citric acid to metal salt is 2:10), stir, heat in a water bath to 80℃ to dissolve and prepare Ni and Fe salt complex solution, recorded as solution b;
[0060] Take 135g of carrier ethyl orthosilicate, add 135g of anhydrous ethanol, stir, heat in a water bath to 80°C to disperse the ethyl orthosilicate, and record it as solution C;
[0061] Slowly add solution c into solution b, stir and heat the mixed solution in a water bath at 80°C, then slowly add solution a into the mixed solution, stir and heat the mixed solution in a water bath at 100°C until the mixed solution becomes viscous, dry at 120°C for 24 hours, and calcine at 750°C for 4 hours in an atmosphere of a mixed gas of N2 and H2 (the volume ratio of N2 to H2 is 9:1) to obtain a Ni-NiFe / SiO2 catalyst.
[0062] Example 3
[0063] Take 36 ml of ammonia water (aqueous solution containing 25% ammonia), heat it to 80°C in a water bath, and record it as solution a;
[0064] Take 145g Ni(NO3)2·6H2O and 111g Fe(NO3)3·9H2O respectively, add 740g deionized water and 30g citric acid (the molar ratio of Ni to Fe is 5:3, and the molar ratio of citric acid to metal salt is 2:10), stir, heat in a water bath to 80℃ to dissolve and prepare Ni and Fe salt complex solution, recorded as solution b;
[0065] Take 95g of carrier ethyl orthosilicate, add 95g of anhydrous ethanol, stir, and heat in a water bath to 80°C to disperse the ethyl orthosilicate, which is recorded as solution C;
[0066] Slowly add solution c into solution b, stir and heat the mixed solution in a water bath at 80°C, then slowly add solution a into the mixed solution, stir and heat the mixed solution in a water bath at 100°C until the mixed solution becomes viscous, dry at 120°C for 24 hours, and calcine at 750°C for 4 hours in an atmosphere of a mixed gas of N2 and H2 (the volume ratio of N2 to H2 is 9:1) to obtain a Ni-NiFe / SiO2 catalyst.
[0067] Example 4
[0068] Take 56 ml of ammonia water (aqueous solution containing 25% ammonia), heat it to 80°C in a water bath, and record it as solution a;
[0069] Take 145g Ni(NO3)2·6H2O and 75g Fe(NO3)3·9H2O respectively, add 580g deionized water and 14g citric acid (the molar ratio of Ni to Fe is 5:2, and the molar ratio of citric acid to metal salt is 1:10), stir, heat in a water bath to 80°C to dissolve and prepare a Ni and Fe salt complex solution, which is recorded as solution b;
[0070] Take 115g of carrier ethyl orthosilicate, add 115g of anhydrous ethanol, stir, heat in a water bath to 80°C to disperse the ethyl orthosilicate, and record it as solution C;
[0071] Slowly add solution c into solution b, stir and heat the mixed solution in a water bath at 80°C, then slowly add solution a into the mixed solution, stir and heat the mixed solution in a water bath at 100°C until the mixed solution becomes viscous, dry at 120°C for 24 hours, and calcine at 750°C for 4 hours in an atmosphere of a mixed gas of N2 and H2 (the volume ratio of N2 to H2 is 9:1) to obtain a Ni-NiFe / SiO2 catalyst.
[0072] Example 5
[0073] Take 16 ml of ammonia water (aqueous solution containing 25% ammonia), heat it to 80°C in a water bath, and record it as solution a;
[0074] Take 145g Ni(NO3)2·6H2O and 75g Fe(NO3)3·9H2O respectively, add 700g deionized water and 40g citric acid (the molar ratio of Ni to Fe is 5:2, and the molar ratio of citric acid to metal salt is 3:10), stir, heat in a water bath to 80℃ to dissolve and prepare Ni and Fe salt complex solution, recorded as solution b;
[0075] Take 115g of carrier ethyl orthosilicate, add 115g of anhydrous ethanol, stir, heat in a water bath to 80°C to disperse the ethyl orthosilicate, and record it as solution C;
[0076] Slowly add solution c into solution b, stir and heat the mixed solution in a water bath at 80°C, then slowly add solution a into the mixed solution, stir and heat the mixed solution in a water bath at 100°C until the mixed solution becomes viscous, dry at 120°C for 24 hours, and calcine at 750°C for 4 hours in an atmosphere of a mixed gas of N2 and H2 (the volume ratio of N2 to H2 is 9:1) to obtain a Ni-NiFe / SiO2 catalyst.
[0077] Comparative Example 1
[0078] Take 145g Ni(NO3)2·6H2O and 75g Fe(NO3)3·9H2O respectively, add 630g deionized water and 26g citric acid, stir, heat in a water bath to 80℃ to dissolve and prepare Ni and Fe salt complex solutions, recorded as solution b;
[0079] Take 115g of ethyl orthosilicate, add 115g of anhydrous ethanol, stir, and heat in a water bath to 80°C to disperse the ethyl orthosilicate, which is recorded as solution C;
[0080] Solution c was slowly added to solution b, and the mixed solution was stirred and heated in a water bath at 100°C until the mixed solution became viscous, dried at 120°C for 24 hours, and calcined at 750°C for 4 hours in an atmosphere of a mixture of N2 and H2 (the volume ratio of N2 to H2 was 9:1) to obtain a NiFe / SiO2 catalyst.
[0081] Comparative Example 2
[0082] Take 16 ml of ammonia water and heat it to 80°C in a water bath, which is called solution a;
[0083] Take 145g Ni(NO3)2·6H2O and 75g Fe(NO3)3·9H2O respectively, add 700ml deionized water, stir, heat in a water bath to 80℃ to dissolve to prepare Ni and Fe salt solutions, recorded as solution b;
[0084] Take 115g of carrier ethyl orthosilicate, add 115g of anhydrous ethanol, stir, heat in a water bath to 80°C to disperse the ethyl orthosilicate, and record it as solution C;
[0085] Slowly add solution c into solution b, stir and heat the mixed solution in a water bath at 80°C, then slowly add solution a into the mixed solution, stir and heat in a water bath at 100°C until the mixed solution becomes viscous, dry at 120°C for 24 hours, and calcine at 750°C for 4 hours in an atmosphere of a mixture of N2 and H2 (the volume ratio of N2 to H2 is 9:1) to obtain a NiFe / SiO2 catalyst.
[0086] Comparative Example 3
[0087] Take 28 ml of ammonia water and heat it to 80°C in a water bath, which is called solution a;
[0088] Take 145g Ni(NO3)2·6H2O and 186g Fe(NO3)3·9H2O respectively, add 820g deionized water and 38g citric acid (the molar ratio of Ni to Fe is 5:5, and the molar ratio of citric acid to metal salt is 2:10), stir, heat in a water bath to 80°C to dissolve and prepare a Ni and Fe salt complex solution, which is recorded as solution b;
[0089] Take 55g of carrier ethyl orthosilicate, add 55g of anhydrous ethanol, stir, heat in a water bath to 80°C to disperse the ethyl orthosilicate, and record it as solution C;
[0090] Slowly add solution c into solution b, stir and heat the mixed solution in a water bath at 80°C, then slowly add solution a into the mixed solution, stir and heat in a water bath at 100°C until the mixed solution becomes viscous, dry at 120°C for 24 hours, and calcine at 750°C for 4 hours in an atmosphere of a mixture of N2 and H2 (the volume ratio of N2 to H2 is 9:1) to obtain a NiFe / SiO2 catalyst.
[0091] Comparative Example 4
[0092] Take 20 ml of ammonia water and heat it to 80°C in a water bath, which is called solution a;
[0093] Take 145g Ni(NO3)2·6H2O, add 450g deionized water and 19g citric acid (the molar ratio of Ni to Fe is 5:0, and the molar ratio of citric acid to metal salt is 2:10), stir, heat in a water bath to 80℃ to dissolve and prepare a Ni salt complex solution, which is recorded as solution b;
[0094] Take 150g of carrier ethyl orthosilicate, add 150g of anhydrous ethanol, stir, heat in a water bath to 80°C to disperse the ethyl orthosilicate, and record it as solution C;
[0095] Slowly add solution c into solution b, stir and heat the mixed solution at 80°C in a water bath, then slowly add solution a into the mixed solution, stir and heat at 100°C in a water bath until the mixed solution becomes viscous, dry at 120°C for 24 hours, and calcine at 750°C for 4 hours in an atmosphere of a mixture of N2 and H2 (the volume ratio of N2 to H2 is 9:1) to obtain a Ni / SiO2 catalyst.
[0096] Comparative Example 5
[0097] Take 20 ml of ammonia water and heat it to 80°C in a water bath, which is called solution a;
[0098] Take 75g Fe(NO3)3·9H2O, add 210g deionized water and 8g citric acid (the molar ratio of Ni to Fe is 0:2, and the molar ratio of citric acid to metal salt is 2:10), stir, heat in a water bath to 80℃ to dissolve and prepare an Fe salt complex solution, which is recorded as solution b;
[0099] Take 220g of carrier ethyl orthosilicate, add 220g of anhydrous ethanol, stir, heat in a water bath to 80°C to disperse the ethyl orthosilicate, and record it as solution C;
[0100] Slowly add solution c into solution b, stir and heat the mixed solution at 80°C in a water bath, then slowly add solution a into the mixed solution, stir and heat at 100°C in a water bath until the mixed solution becomes viscous, dry at 120°C for 24 hours, and calcine at 750°C for 4 hours in an atmosphere of a mixture of N2 and H2 (the volume ratio of N2 to H2 is 9:1) to obtain Fe / SiO2 catalyst.
[0101] The catalyst TPR spectra of the embodiments and comparative examples are as follows: Figure 2 The reduction peak of Ni-NiFe in the embodiment is located at 340℃~700℃, showing a strong continuous "steamed bun peak" shape, while the reduction peak of Ni-NiFe in the comparative example is located at 300℃~600℃, showing a weak continuous "steamed bun peak", which indicates that a special force is formed between Ni and NiFe in the embodiment, and the force is stronger than that in the comparative example.
[0102] Catalyst performance test:
[0103] The performance of the catalyst was evaluated in a quartz tube furnace. The catalyst was loaded into a reactor and reduced for 1 hour by introducing a mixture of N2 and H2 (the volume ratio of N2 to H2 was 9:1). The raw gas CH4 and N2 mixture was introduced for reaction, and nitrogen was purified. The methane content was analyzed by chromatography. The life of the catalyst was determined by detecting whether the methane content in the tail gas was close to the feed content. The results are shown in Table 1.
[0104] Test conditions: catalyst loading 3g, temperature: 750℃, pressure: 0.1MPa, volume space velocity 500h -1 , N2:CH4 volume ratio = 4:1, nitrogen purification for 1h.
[0105] Table 1 Catalyst life of Examples and Comparative Examples
[0106] catalyst Reaction temperature / ℃ Catalyst life Comparative Example 1 750 10h Comparative Example 2 750 8h Comparative Example 3 750 10h Comparative Example 4 750 6h Comparative Example 5 750 7h Example 1 750 42h Example 2 750 38h Example 3 750 37h Example 4 750 40h Example 5 750 36h
[0107] As can be seen from Table 1, the example catalyst Ni-NiFe / SiO2 prepared by the present invention through citric acid complexed metal salt, ethanol dispersion carrier precursor tetraethyl orthosilicate, and coupled ammonia complexation has a long life at 750°C, while the life of the comparative catalyst is significantly lower than that of the example catalyst.
[0108] The TEM images of carbon nanotubes generated by the reaction of Example 1 and Comparative Example 1 are as follows: Figure 3 and Figure 4 As shown, it can be seen that the carbon nanotubes generated in Example 1 have the characteristics of high hollow ratio, few branches, strong continuity and uniform diameter, while the carbon nanotubes in Comparative Example 1 have lower hollow ratio, more branches, bamboo-like shape and lower diameter uniformity.
[0109] The SEM image of the carbon nanotubes generated by the reaction of Nima Bayat and Example 1 is shown in FIG. Figure 5 and Figure 6 As shown, it can be seen that the carbon nanotubes generated by the reaction using the catalyst of the background technology are sparsely distributed and short, while the carbon nanotubes generated by the reaction of Example 1 have fewer branches, strong continuity, are dense and long, and the morphology of the carbon nanotubes is significantly improved.
[0110] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A method for preparing a nickel-based catalyst, characterized in that: The following steps are involved: S1, heating ammonia water to obtain solution a; S2, mixing and heating nickel salt, iron salt, water and citric acid to prepare solution b, wherein the molar ratio of Ni to Fe is 5:1 to 5:3, and the molar ratio of citric acid to metal salt is 1:10 to 3:10; S3, mixing ethyl orthosilicate and anhydrous ethanol and heating them to prepare solution C; S4. Add solution c to solution b, mix and heat, then add solution a, mix and heat until the mixed solution becomes viscous, dry, and calcine in a mixed atmosphere of N2 and H2 to obtain a nickel-based catalyst.
2. The preparation method according to claim 1, characterized in that: In step S1, the concentration of ammonia water is 25% to 28%; In step S1, the heating temperature is 60°C to 80°C.
3. The preparation method according to claim 1, characterized in that: In step S2, the nickel salt includes one or more of nickel nitrate, nickel sulfate, and nickel acetate; the iron salt includes one or more of iron nitrate, iron sulfate, and iron acetate.
4. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the metal salt to water is 0.2 to 0.4; In step S2, the heating temperature is 60°C to 80°C.
5. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of ethyl orthosilicate to anhydrous ethanol is 1 to 3; In step S3, the heating temperature is 60°C to 80°C.
6. The preparation method according to claim 1, characterized in that: In step S4, the heating temperature after adding solution c to solution b is 60°C to 80°C; In step S4, the heating temperature after adding solution a is 60°C to 800°C.
7. The preparation method according to claim 1, characterized in that: In step S4, the ratio of ethyl orthosilicate, metal salt and ammonia water in the mixed solution is 90-140 g: 180-260 g: 16-36 mL; In step S4, the volume ratio of N2 to H2 is 4:1 to 10:1; In step S4, the calcination temperature is 650-850° C., and the calcination time is 4-6 hours.
8. A nickel-based catalyst, characterized in that The invention is prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the nickel-based catalyst according to claim 8 in preparing carbon nanotubes by cracking methane.
10. The use according to claim 9, characterized in that: The application includes: placing the nickel-based catalyst in a reactor, introducing a mixed gas of N2 and H2 for reduction for 0.5-1.5 hours, then introducing a mixed gas of CH4 and N2 for reaction to crack the catalyst to generate carbon nanotubes, and introducing nitrogen after the reaction to purify the carbon nanotubes; The reaction conditions are: reaction temperature is 700-800°C, reaction pressure is 0.1-0.2MPa, volume space velocity is 400-600h -1 , the volume ratio of N2 to CH4 is 4:1 to 1:1.
Citation Information
Patent Citations
Magnetic Fe3O4 / SiO2 / TiO2 / quantum dot compounded nanometer photocatalyst and preparation method and application thereof
CN102921435A
Carboxyl containing organic matter assisted preparation method for metal and high-dispersion metal catalyst
CN103170637A
Hollow spherical shell carrier loaded nickel-based alloy catalyst and preparation method thereof
CN112221502A
Alkaline water electrolysis method and anode for alkaline water electrolysis
CN115244220A
Preparation method of aluminum bronze alloy
CN118639148A